The Influence of Fashion Trends, Product Quality, and Prices on Thrift Purchasing Decisions in Muhmmadiyah University Surakarta Students - Fitri, Nabiilah Aditia; Asmawan, Moh Chairil (Universitas Muhammadiyah Surakarta, 2024)
The purpose of this research is to examine the influence of fashion trends, product quality and price on thrift purchasing decisions among Muhammadiyah University Surakart students. The type of research used by researchers is quantitative with a correlational research design. The instrument used in this research was a questionnaire using the Google Form platform. The place of research was carried out at the Muhammadiyah University of Surakarta. The population in this study were 92 active students of the Accounting Education Study Program at Muhammadiyah University of Surakarta with a research sample of 62 respondents. The data analysis technique used is multiple regression analysis technique. From the analysis of existing data, the following research results were obtained: 1) fashion trends have a negative effect on purchasing decisions with a calculated t value of 0.597; 2) product quality has a positive effect on purchasing decisions with a calculated t value of 0.155; 3) price has a positive effect on purchasing decisions with a calculated t value of 0.002; 4) fashion trends, product quality and price have a significant influence on purchasing decisions with a calculated f value of 9.159.